Perspectives and Trends in Organizational Knowledge Management - Lima, José Jerônimo de Menezes; Menezes, Luciana Hahn de; Teixeira, Maria do Rocio Fontoura; Redaelli, Emir José (Seven Editora, 2023)
This article examines the perspectives and trends in organizational knowledge management. The perspectives were obtained from the perception of managers who are experts in the field of statements about the decline of this field of study in the academic and business environment, as well as from practical experiences in the implementation of knowledge management projects in companies, based on a case study. The trends were obtained from the review of the specialized academic and commercial literature on the use of knowledge management in companies. This qualitative research used the case study method, carried out in an information technology company that executes the information technology policy in the State of Rio Grande do Sul, Brazil. For data collection, primary and secondary documents of the company were analyzed, a questionnaire was applied with open, exploratory questions, and semi-structured interviews with confirmatory questions were conducted. Regarding the perspectives, the results found show the vitality of the field of study today and show the evolution of its use by companies and the perception of specialist managers about criticisms and pessimistic statements about this field of study offers an overview of how it is currently being approached and the directions it is taking at the academic and business level. The results suggest the possibility of a conceptual and practical reformulation of the field of study, given the evolution of the theme, to keep up with technological changes. They also highlight the development of automated mechanisms for knowledge flows that can be leveraged by artificial intelligence. They show companies' emphasis on implementing standards for knowledge management, such as ISO-9001 and ISO-30401, conducting audits to ensure the effectiveness of knowledge management programs, advances in adopting practices to improve organizational learning based on collective intelligence, increasing use of communities of practice, emphasis on competitive intelligence, and data privacy concerns. Regarding the trends in the field of study, the results found indicate an emphasis on lean project management, attention to information sharing for remote work, actions aimed at absorptive capacity and organizational ambidexterity, intensive use of data analysis, alignment with themes of Society 5.0 and sustainability, use of maturity models, and the impact of artificial intelligence. The relevance of the research lies in the adoption of a critical approach to the field of study, bringing theoretical contributions and implications at the practical level, in addition to suggesting the realization of future studies for empirical validation of knowledge management projects. DOI:https://doi.org/10.56238/sevened2023.006-081